Disaster education as an effort to improve students' flood mitigation preparedness - Erman Syarif; Maddatuang Maddatuang; Alief Saputro; Steve Carver; Susan L Cutter (Universitas Negeri Malang, 2023)
Reducing disaster risk is an important thing that needs to be done at all levels of society, including students. This study aims to determine students' level of preparedness for flood disasters and the efforts made by schools in dealing with flood disasters. This study used a descriptive quantitative method conducted at SMA Negeri 1 Jeneponto. The population in this study was 95 students, with a total sample of 49 students determined using the Slovin formula with a ten percent margin of error. The data collection techniques used questionnaires, interviews, and documentation. The research results were analyzed using descriptive statistics. The results of the study showed that knowledge of attitudes, emergency response plans, disaster warning systems, and students' disaster preparedness when a flood disaster occurs are included in the